FIRST RECORD OF BRACHYLAIMA MAZZANTII TRAVASSOS, 1927 IN DOMESTIC PIGEON (COLUMBA LIVIA) IN PERU - Naupay-Igreda, Asucena (2014)
In order to evaluate the Helminth fauna of Columba livia from the Cercado de Lima, 55 pigeons were captured between October 2012 and November 2013. Through necropsy of a pigeon produced 53 trematodes located along the small intestine. 15 specimens were stained with Shemichon'sacetic carmine and identified as Brachylaima mazzantii Travassos, 1927. Intraspecific morphological variations were observed (some specimens had slightly sinuous intestinal loops larger than the posterior testis). This contribution is the first record of the presence of B. mazzantii in the domestic pigeon Lima-Peru.